Rapid Scanning Electron Microscopy Detection and Sequencing of Severe Acute Respiratory Syndrome Coronavirus 2 and Other Respiratory Viruses - Haddad, Gabriel; Bellali, Sara; Fontanini, Anthony; Francis, Rania; La Scola, Bernard; Levasseur, Anthony; Bou Khalil, Jacques; Raoult, Didier (Frontiers in Microbiology, 2020)
There is an urgent need for accurate and rapid testing methods to quickly identify infected patientsas well as asymptomatic carriers, in order to prevent the spread of emerging viruses. Here, we developed a rapid testing strategy by scanning electron microscopy capable of detecting SARS-CoV-2 and other respiratory viruses directly from patients. We evaluated our results by comparing them to RT-PCR and metagenomic sequencing results.We correlated the presence of the SARS-CoV-2 to the viral load, where samples with Ct values lower than 18 were all detected by SEM. The sensitivity deacresed progressively with higher Ct values.In addition, we found a correlation with metagenomic sequencing, where all samples detected by SEM were sequenced and viral sequences were easily recovered. Following this study, SEM proved its efficiency as a frontline method for directly detecting previously unknown microorganisms that cannot be targeted by molecular methods and can cause potential outbreaks.